Number meaning and number grammar in English and Spanish - Bock, Kathryn; Carreiras, Manuel; Meseguer, Enrique (Journal of memory and language, 2012)
► Tests how grammatical agreement systems affect nonlinguistic number apprehension. ► Shows similar reliance on notional number by English and Spanish speakers. ► Disputes claims of crosslinguistic differences in notional effects on verb agreement. ► Challenges linguistic relativity accounts. ► Rich morphology does not enhance use of notional properties in grammatical agreement. Grammatical agreement makes different demands on speakers of different languages. Being widespread in the languages of the world, the features of agreement systems offer valuable tests of how language affects deep-seated domains of human cognition and categorization. Number agreement is one such domain, with intriguing evidence that typological characteristics of number morphology are associated with differences in sensitivity to number distinctions. The evidence comes from research on language production that points to the morphological richness of languages as enhancing the expression of number distinctions. To critically test this hypothesis, native speakers of a sparse-morphology language (English) were compared with native speakers of a rich-morphology language (Spanish) in their use of semantically and grammatically motivated number agreement. With meaning-matched materials, speakers of both languages displayed significant variations in number agreement due to implicit nuances of number semantics, and the patterns and magnitudes of interaction with grammatical number were the same for both groups. In this important respect, speakers of English and Spanish appear to construe numerosity in similar ways, despite the substantial morphological and syntactic differences in their languages. The results challenge arguments that language variations can shape the apprehension of nonlinguistic number or promote differential expression of number meaning during the production of grammatical agreement.